Increasing creativity, production innovation and commercialization through the new teaching factory model based on life skills - Cucu Sutianah; Bandi Sobandi; Alfian Azhar Yamin; Phan Doang Kieu Trang (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2024)
This research aims to implement and develop a new teaching and learning factory model based on life skills in Vocational Secondary Education (SME) Creative and Production Crafts Expertise Program. This model is designed to support the needs of the Industrial Revolution 4.0 by integrating project-based learning through collaboration between the school curriculum and the industrial world. This research usesmixed methods, with a quasi-experimental design involving control and experimental groups using pre-test and post-test. The results showed that the new teaching and learning factory model was valid and reliable based on expert validation tests. The implementation of this model successfully increased students' creativity in product design, production, and commercialisation, and it developed social skills such as critical thinking, communication, collaboration, and interpersonal skills. In conclusion, the implementation of the life skills-based teaching factory model is effective in preparing students to face the challenges of the world of work, improving innovation skills, and supporting production processes that are relevant to industry needs. The contribution of this research is in the development of an innovative learning model that integrates the education curriculum with the world of work, thus producing graduates who are better prepared to face the challenges of the Industrial Revolution 4.0.